Extracellular Vesicles and Their Importance in Human Health 2020
DOI: 10.5772/intechopen.85117
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Cancer

Abstract: Extracellular vesicles (EVs) represent a generic term for all the secreted vesicles, which include exosomes, microvesicles, and apoptotic bodies. EVs are key partners in the intercellular communication and play an essential role in multiple physiological and pathological conditions. EVs are shuttles for cargo molecules, such as RNA (mRNA, microRNA, and other noncoding RNAs), DNA, proteins (receptors, transcription factors, enzymes, and extracellular matrix proteins), and lipids. In pathological states, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 162 publications
1
16
0
Order By: Relevance
“…Several studies also confirm in vivo what was already known from in vitro observation: tumor cells release far more EVs than normal counterpart [108][109][110]. Thus, quantitative or qualitative EVs modifications could provide useful information [111].…”
Section: Breast Cancer Evs As Biomarkers In Clinical Applicationssupporting
confidence: 70%
“…Several studies also confirm in vivo what was already known from in vitro observation: tumor cells release far more EVs than normal counterpart [108][109][110]. Thus, quantitative or qualitative EVs modifications could provide useful information [111].…”
Section: Breast Cancer Evs As Biomarkers In Clinical Applicationssupporting
confidence: 70%
“…Aberrant miRNA expression was found in tumors and biological fluids. More and more data show that miRNAs could be excreted into circulation via extracellular vesicles or bound to proteins such as AGO or high-density lipoprotein (HDL) (Larrea et al, 2016;Voichitoiu et al, 2019). Thus, circulating miRNAs may serve as a reflection of the underlying disease, but this approach is hampered for the moment by the complicated and lengthy PCR-based procedures used by most laboratories.…”
Section: Main Technologies That Are Used For Mirna Identification Fromentioning
confidence: 99%
“…Many studies have shown that EVs are produced by both prokaryotes and eukaryotes, indicating a persistent evolution of their signaling mechanism during a time, giving EVs an increasingly important role in the future [3,4]. In general, EVs from the human blood are derived from platelets, but they can also be released from leukocytes, erythrocytes, endothelial cells, smooth muscle cells, and even cancer cells [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The content of EVs can vary to a great extent (lipids, proteins, nucleic acid species) and depends on the cell of origin [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation